Implementation of Authentic Assessment of Reading Skills For Grade 4 in Independent Curriculum in Elementary School 205/IV Jambi City - Hendriani, Hendriani; Nazurty, Nazurty; Widowati, Atri (Journal of Innovation and Research in Primary Education, 2025)
The curriculum changes in Indonesia, from KTSP to the Merdeka Curriculum, aim to improve the quality of education by emphasizing 21st-century skills and the Pancasila Student Profile. One of the key aspects of the Merdeka Curriculum is the implementation of authentic assessment, which encompasses affective, cognitive, and psychomotor domains. However, many teachers face difficulties in understanding and applying this, particularly in reading skills. This study aims to analyze teachers’ perceptions of the implementation of authentic assessment in reading skills at SDN 205/IV in Jambi City. The research employs a qualitative approach using a phenomenological study. Data were collected through observation, unstructured interviews, and documentation, and were analyzed inductively using thematic coding, verification, and data triangulation. The findings show that teachers’ understanding of authentic assessment varies. Five fourth-grade teachers experienced difficulties in its implementation due to time constraints, lack of training, and low student motivation in reading. Authentic assessments were carried out through observation, written tests, oral tests, and the provision of feedback to enhance students’ understanding. To overcome these challenges, teachers applied strategies such as observation journals, differentiated instruction, and reflective discussion techniques to improve the effectiveness of reading instruction.